Improving Macroeconomic Management: Experiences and Lessons - Basyal, Tula Raj (NRB Economic Review, 2023)
The relationship between growth and macroeconomic stability is a wellestablished phenomenon. Long-term growth requires a higher level of investment and a stable economic environment contributes in promoting saving and investment. Good macroeconomic policies help attract foreign saving. Sound fiscal and monetary policies create a conducive climate for private investment and economic growth. So, the policymakers need to redress the problems of domestic and external financial imbalances by designing and implementing an appropriate mix of policies for achieving higher growth, lower price uncertainty, reduced external imbalances, and other macroeconomic vulnerabilities. So, the important issues facing the policymakers are designing sound exchange rate arrangement, making current account sustainable, and promoting financial and macroeconomic stability. In order to promote sound macroeconomic environment for attaining sustained economic growth, there is a need to pursue more flexible exchange rate regime and make progress toward adopting inflation targeting in addition to improving the financial sector soundness, strength and stability.